PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP TINGKAT KONSUMTIFISME PADA REMAJA DI KOTA TANGERANG - Setyaningtyaz, Sabrina; Zahra Hasbullah, Nadifa; Rizqi Amani , Rahma; Prisyilia azzahra, Ghefira; Aditya, Toddy (Gapenas Publisher, 2025)
This study examines the impact of social media usage intensity on consumerism levels among adolescents in Tangerang. With approximately 99% of teenagers aged 13-18 actively engaging on platforms like Instagram and TikTok, the research highlights both positive and negative consequences. Social media enhances connectivity and provides easy access to information, yet it also exposes youth to risks such as cyberbullying, unrealistic beauty standards, and addiction. The findings indicate a significant correlation between high social media usage and increased consumer behavior, driven by targeted advertising and influencer culture. This underscores the necessity for financial literacy and responsible social media practices among adolescents to mitigate adverse effects while maximizing benefits. The study employs a quantitative approach, utilizing a correlational design to analyze data collected from 400 respondents through questionnaires. Results demonstrate a strong positive correlation between social media usage and consumerism, suggesting that increased exposure to marketing content influences adolescents' purchasing decisions. By addressing the psychological implications of social media on youth, this research contributes to understanding the broader societal impacts of digital engagement on consumer behavior. Ultimately, the study advocates for guidance from parents and educators to foster healthier online habits among adolescents, ensuring that social media serves as a tool for positive development rather than a catalyst for detrimental consumerist tendencies.